Effective Use of E-Money through Online Shopping in E-Commerce: English - Givan, Bryan; Amalia, Rizky; Abdurrachman, Abdurrachman; Sari, Imelda; Heri Winarno, Slamet; Arman Syah Putra (International Journal of Educational Research & Social Sciences, 2021)
The background of the problem raised in this study is how to measure the effectiveness of using e-money for online shopping on an e-commerce shopping system. With the use of Imani, the use of cash will be limited so that it will be able to do more transactions on online shopping in e-commerce. The method used in this study is to use quantitative methods by conducting a survey to 100 users of online shopping in e-commerce, with the results of the survey, the data can be processed so that it can be seen whether the direction of the hypothesis raised in this study is directly proportional or proportional. The problem raised in this study is how to measure the effectiveness of a payment, especially payments using electronic money media. Therefore, with a non-cash payment system, the effectiveness of the payment will be known. The purpose and objective of this research is to find out how the effectiveness of using electronic money in payment systems that are carried out online and used in various places so that many transactions are carried out only using electronic money and not using cash.